The role of riparian buffers in the provision of hydrologic ecosystem services across an urban landscape considering climate change - Stanton, Jessica Jane (Kansas State University, 2020)
An estimated 66% of the total global population will live in urban areas by 2050 (Salerno, Gaetano, & Gianni, 2018). Urbanization causes various environmental impacts ranging from habitat loss to altered hydrologic processes, which stem from increased runoff volume and rate, reduced infiltration, and decreased time of concentration (US EPA, 2018; Wakode et al, 2017). Thus, man-made and natural waterways will have to convey a larger volume of surface runoff than ever before. The evaluation of potential changes in hydrologic functionality represented by changes in runoff, infiltration, and flooding risk must become a key component of land management and watershed planning as “urbanization without sound management would increase flood risks” (Ahiablame & Shakya, 2016). The overall goal of this research was to develop a deeper understanding of the role of riparian buffers in provision of flood regulating hydrologic ecosystem services (HESs) in an urbanizing watershed. Indicators of flood regulation quantified in this research include changes in total inflow volume and peak inflow. Historic (event-based and continuous) and climate change precipitation data (CMIP5), in conjunction with four riparian buffer land use scenarios, were used to evaluate the impact of climate change and riparian buffer management on HES provision in the Blue River Watershed in the Kansas City area using PCSWMM modeling software. Results indicated riparian buffer restoration around all streams including ephemeral streams offers the greatest flood regulating HESs, providing significant total inflow reduction across the watershed and more frequent reduction of peak inflow. Flood regulating HESs were still provided when the riparian buffer was restored around main channels only but to a much lesser extent. Similar trends were observed under event-based and continuous model simulations. While the datasets utilized in this study are site specific, the findings are widely applicable. With the threat of urbanization and climate change on the rise, policy makers should use these findings to support creation of policy to restore and protect riparian areas.
Keywords: Watershed modeling; Hydrologic ecosystem services; Climate change; Urbanization; Riparian buffer; System resiliency